A Study Of Mobile Communication In Malaysia: Identifying The Potential Market Segment And The Key Success Factors Influencing The 3G Services Rollout - Sakrani, Kamarul Halim (2006)
The objective of this study are to identify the potential market segment and the key success factors that will influence the 3G services rollout in Malaysia.